Nuns as historians in early modern Germany - Woodford, Charlotte (Oxford modern languages and literature monographs., 2002)
The literary history of early modern German convents is a much neglected field. Nuns' writings were rarely printed and generally only read within their own institution. This text is an overview of nuns' literary activities in this period.